The last painting of Sara De Vos [large type] - Smith, Dominic, 1971- (Thorndike Press, 2016)
A rare seventeenth-century painting -- the only known surviving work of a woman who defied the expectations of her time -- links three lives, on three continents, over three centuries in this exhilarating new novel from the critically acclaimed author of The Beautiful Miscellaneous.